2012
DOI: 10.1177/0961203311429318
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity following Hepatitis B vaccine as part of the spectrum of ‘Autoimmune (Auto-inflammatory) Syndrome induced by Adjuvants’ (ASIA): analysis of 93 cases

Abstract: Common clinical characteristics were observed among 93 patients diagnosed with immune-mediated conditions post-HBVv, suggesting a common denominator in these diseases. In addition, risk factors such as history of autoimmune diseases and the appearance of adverse event(s) during immunization may serve to predict the risk of post-immunization diseases. The ASIA criteria were found to be very useful among adults with post-vaccination events. The application of the ASIA criteria to pediatric populations requires f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 44 publications
3
49
0
6
Order By: Relevance
“…Recently, a clinical syndrome referred to as 'autoimmune/ autoinflammatory syndrome induced by adjuvant' (ASIA), encompassing four different clinical entities, namely siliconosis [28,29], the 'gulf war syndrome' [30], macrophagic myofasciitis syndrome [31] and post-vaccination phenomena [29,[32][33][34], has been described in humans. The symptoms are overlapping and have been attributed to the probable effect of adjuvants (reviewed in [35][36][37][38]).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a clinical syndrome referred to as 'autoimmune/ autoinflammatory syndrome induced by adjuvant' (ASIA), encompassing four different clinical entities, namely siliconosis [28,29], the 'gulf war syndrome' [30], macrophagic myofasciitis syndrome [31] and post-vaccination phenomena [29,[32][33][34], has been described in humans. The symptoms are overlapping and have been attributed to the probable effect of adjuvants (reviewed in [35][36][37][38]).…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective study, Zafrir et al performed an analysis of patients from various centers in the United States who developed symptoms of autoimmune diseases after hepatitis B vaccination, notably the vaccine containing Al. From a group of 93 patients analyzed by Zafrir et al, a cohort of 49 was serologically evaluated and 80% showed the presence of autoantibodies (57% evaluated subjects had ANA antibodies, and 28% had rheumatoid factor) [14].…”
Section: S T R E S Z C Z E N I Ementioning
confidence: 99%
“…W badaniach na zaszczepionych zwierzętach stwierdzono pojawienie się różnych autoprzeciwciał, w tym typowych dla tocznia układowego (u psów) [14]. W badaniach na łososiach po podaniu olejowego adiuwantu do otrzewnej obserwowano powstanie przeciwciał przeciwjądrowych, przeciwciał przeciw β2-glikoproteinie I (β2-GPI) oraz antyferrytynowych, a także chorobę ziarniniakową otrzewnej i wątroby, zapalenie kłębuszków nerkowych oraz powikła-nia zakrzepowo-zatorowe [12].…”
Section: S T R E S Z C Z E N I Eunclassified
See 1 more Smart Citation
“…The mean age of onset, the great prevalence of neurological disturbances and general symptoms suggest an overlap between chronic fatigue syndrome and fibromyalgia in ASIA. Indeed, Zafrir et al [8] already could identify central pain syndrome in 20.5 % of the cases, suggesting that HBVv may be associated in some cases with the onset of chronic fatigue syndrome and fibromyalgia. It must be underlined that chronic fatigue syndrome and fibromyalgia are often associated with autoimmune disorders and represent a burden for a relatively high percentage of patients with Sjögren's syndrome [9].…”
mentioning
confidence: 99%